2000
DOI: 10.1116/1.1314394
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of step coverage change in ultraviolet-transparent plasma enhanced chemical vapor deposition silicon nitride films

Abstract: Ultraviolet (UV)-transparent silicon nitride films were deposited in a plasma enhanced chemical vapor deposition reactor. The dependence of the film properties on process parameters has been studied. UV transmittance, refractive index, hydrogen content, and step coverage were compared to UV-opaque films. A significant difference in film growth between UV-opaque and UV-transparent SiNx layers has been detected. When film properties shift to an increased UV transparency, step coverage worsens significantly. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This was experimentally ascertained in previous studies, in which the RI was strongly correlated to the Si/N ratio [1] or SiH/NH [7]. It has also been observed that the relationship is valid only at higher SiH NH ratio [2], [7]. The increase is consistently observed for all temperatures.…”
Section: Effects Of Nh Flow Rate and Substratesupporting
confidence: 73%
See 1 more Smart Citation
“…This was experimentally ascertained in previous studies, in which the RI was strongly correlated to the Si/N ratio [1] or SiH/NH [7]. It has also been observed that the relationship is valid only at higher SiH NH ratio [2], [7]. The increase is consistently observed for all temperatures.…”
Section: Effects Of Nh Flow Rate and Substratesupporting
confidence: 73%
“…The represents the gradient of the bipolar sigmoid function and determines the activation level of neuron. Meanwhile, the BPNN adopts a linear function in the output layer, expressed as (2) where represents the gradient of the linear function. For a given set of training factors, both gradients in (1) and (2) are to be optimized to improve the prediction accuracy.…”
Section: Fundamentals Of Neural Networkmentioning
confidence: 99%
“…The major impact of the distance between electrodes, as demonstrated in figure 21, is on the uniformity of the deposited silicon nitride film. The electrode spacing variation has a minor diminishing effect on average deposition rate [64]; however, its effect on the local distribution of deposition rate is indispensable. According to Kushner [65] the deposition rate has generally been observed to decrease with increasing electrode separation.…”
Section: 35mentioning
confidence: 99%
“…Machida improved the film step covering by adding bias [22]. Bierner et al studied the effect of the ratio of gaseous reactants on step coverage in the PECVD of silicon nitride [23]. Özkol et al deposited hydrogenated amorphous silicon (a-Si:H) films by PECVD and studied the relationship between the conformality of a-Si:H films and deposition temperature [24].…”
Section: Introductionmentioning
confidence: 99%